FeNi3–FeNi3N – a high-performance catalyst for overall water splitting. Issue 12 (9th November 2020) - Liang, Shuqin; Jing, Meizan; Thomas, Tiju; Liu, Jian; Guo, Haichuan; Attfield, J. Paul; Saad, Ali; Shen, Hangjia; Yang, Minghui
Abstract : A bifunctional material which has high performance towards overall water splitting in alkaline media is developed by coupling FeNi3 N and FeNi3 in nanoscale. Abstract : The design and development of non-precious metal catalysts with high activity and stability for overall water splitting remains a major challenge. Herein, lamellar FeNi3 N incorporated by FeNi3 is synthesized via thermal ammonolysis. The abundance of hollow sites in this FeNi3 –FeNi3 N heterostructure significantly enhances the intrinsic activity towards hydrogen evolution reaction, while the heterostructure also offers high electrochemical active surface area for oxygen evolution reaction. FeNi3 –FeNi3 N enables a lower overpotential for both hydrogen and oxygen evolution electrocatalysis in alkaline media. When FeNi3 –FeNi3 N is employed as a bifunctional material for overall water splitting, it shows a cell voltage of only 1.5 V at 10 mA cm −2 and offers stable performance for up to 48 h at current densities of ∼40 mA cm −2 .